Implementation of the Complaint Service Application at the Human Resources Bureau Division of the Bangka Belitung District Police Based on Android - Hafish Mairendra Pratama; Chandra Kirana; Delpiah Wahyuningsih (STIKOM Tunas Bangsa Pematangsiantar, 2025)
Digital transformation in human resource (HR) management within government institutions requires innovative solutions to enhance efficiency and transparency. The HR Bureau Division of the Bangka Belitung Islands Police (Polda Kep. Bangka Belitung) currently faces challenges with its manual complaint management system, leading to delays in grievance handling. This study aims to develop and implement an Android-based complaint service application to facilitate effective reporting and monitoring of complaints. The system development methodology employs the Software Development Life Cycle (SDLC), encompassing planning, requirement analysis, design, implementation, testing, and maintenance phases. The results indicate that the developed application successfully meets user needs with key features such as complaint submission, complaint history, and user guidelines. Blackbox testing confirms that all functions operate as expected. This application is expected to improve accountability and efficiency in the complaint handling process within the HR Bureau Division, while also supporting e-government policies.